Rational and design of the ROTAS study: a randomized study for the optimal treatment of symptomatic patients with low-gradient severe aortic valve stenosis and preserved left ventricular ejection fraction. (18th March 2020) - Galli, Elena; Le Ven, Florent; Coisne, Augustin; Sportouch, Catherine; Le Tourneau, Thierry; Bernard, Anne; Bière, Loic; Habib, Gilbert; Lancellotti, Patrizio; Lederlin, Mathieu; Tribouilloy, Christophe; Oger, Emmanuel; et al.
Abstract: Aims: Fifteen to thirty percentage of patients with severe aortic stenosis (AS) have preserved left ventricular ejection fraction (LVEF) and a discordant AS pattern at Doppler echocardiography, which is characterized by a small (<1 cm 2 ) aortic area and low mean aortic gradient (<40 mmHg). The 'Randomized study for the Optimal Treatment of symptomatic patients with low-gradient severe Aortic Stenosis and preserved left ventricular ejection fraction' (ROTAS trial) aims at demonstrating the superiority of aortic valve replacement vs. a 'watchful waiting strategy' in symptomatic patients with low-gradient (LS), severe AS, and preserved LVEF, stratified according to indexed stroke volume, in terms of all-cause mortality or cardiovascular-related hospitalization during follow-up (FU). Methods and results: The ROTAS trial will be a multicentre randomized non-blinded study involving 16 reference centres. AS severity will be confirmed by a multimodality approach (rest and stress echocardiography, calcium scoring, and cardiac magnetic resonance imaging for optimally characterize the population), which could provide important inputs to improve the pathophysiological understanding of this complex disease. Well-characterized patients will be randomized according to the management strategy. The primary endpoint will be the occurrence of all-cause mortality or cardiac related-hospitalizations during 2-year FU. One hundred and eighty subjects per group will be included. Conclusion: The management of patients with LS severe AS and preserved LVEF is largely debated. ROTAS trial will allow a comprehensive evaluation of this particular pattern of AS and will establish which is the most appropriate management of these patients.